2013
DOI: 10.1021/jm400793v
|View full text |Cite
|
Sign up to set email alerts
|

Explorations of Substituted Urea Functionality for the Discovery of New Activators of the Heme-Regulated Inhibitor Kinase

Abstract: Heme-regulated inhibitor kinase (HRI), an eukaryotic translation initiation factor 2 alpha (eIF2α) kinase, plays critical roles in cell proliferation, differentiation, and adaptation to cytoplasmic stress. HRI is also a critical modifier of hemoglobin disorders such as β-thalassemia. We previously identified N,N′-diarylureas as potent activators of HRI suitable for studying biology of this important kinase. To expand the repertoire of chemotypes that activate HRI we screened a ~1,900 member N,N′-disubstituted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 36 publications
0
26
0
Order By: Relevance
“…Similar results have now been corroborated in vitro and in vivo by using another chemotype, 1-((1,4- trans )-4-arylox-ycyclohexyl)-3-arylureas (cHAUs) that directly activate HRI. Lead cHAUs similarly activate HRI, induce eIF2α phosphorylation, and inhibit cancer cell proliferation in vitro and melanoma xenograft growth in vivo [34,62]. …”
Section: Introductionmentioning
confidence: 99%
“…Similar results have now been corroborated in vitro and in vivo by using another chemotype, 1-((1,4- trans )-4-arylox-ycyclohexyl)-3-arylureas (cHAUs) that directly activate HRI. Lead cHAUs similarly activate HRI, induce eIF2α phosphorylation, and inhibit cancer cell proliferation in vitro and melanoma xenograft growth in vivo [34,62]. …”
Section: Introductionmentioning
confidence: 99%
“…Extensive work from our laboratory has demonstrated that EPA, CLT, and certain di -substituted urea analogs [33, 35, 36] induce phosphorylation of eIF2α and thereby reduce the amount of the ternary complex. We have further shown that reducing the amount of the ternary complex downregulates expression of oncogenic proteins such as cyclin D1 and up-regulates expression of ATF-4 and genes under its transcriptional control [32, 34, 35].…”
Section: Discussionmentioning
confidence: 99%
“…Several novel chemical agents that activate eIF2α kinases have recently been identified [33, 36, 37]. The availability of the three dimensional structure of eIF2α kinases PKR and PERK [5658] could further sped up the development of these agents.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations